ACTR-24. A RANDOMIZED PHASE II TRIAL OF VELIPARIB (V), RADIOTHERAPY (RT) AND TEMOZOLOMIDE (TMZ) IN PATIENTS (PTS) WITH UNMETHYLATED MGMT (uMGMT) GLIOBLASTOMA (GBM): THE VERTU STUDY. (11th November 2019) - Khasraw, Mustafa; Leanne McDonald, Kerrie; Rosenthal, Mark; Lwin, Zarnie; Ashley, David; Wheeler, Helen; Barnes, Elizabeth; Foote, Matthew; Koh, Eng-Siew; Sulman, Erik; Back, Michael; Buckland, Michael; et al.
Abstract: BACKGROUND: TMZ offers minimal benefit in pts with de novo uMGMT GBM. V is synergistic with RT and TMZ in uMGMT preclinical GBM models, safe when combined with either RT or TMZ clinically, but the triplet (V+RT+TMZ) is poorly tolerated. VERTU tested V in pts with uMGMT GBM. METHODS: VERTU is a randomized Phase 2 trial comparing Standard Arm (Arm A), RT (60Gy/30 fractions) + TMZ (75mg/m 2 daily) followed by TMZ (150–200mg/m 2 D 1–5) every 28 days for 6 cycles vs Experimental Arm (Arm B), RT (60Gy/30 fractions) + V (200mg PO BID) followed by TMZ (150–200mg/m 2 D 1–5) + V (40mg bid, D 1–7) every 28 days for 6 cycles in pts with de novo uMGMT GBM according to centralised testing. RESULTS: 125 pts were randomized 1:2 (41:84). The 2 groups were matched for age, sex, performance status and extent of resection. Median follow-up was 25.8 months and 91 pts had died. The 6-month Progression-Free Survival (6mPFS) for Arms A and B were 34% (95% CI 20–48) and 46% (95% CI 36–57) respectively. The median PFS for Arms A and B were 4.2m (95% CI 2.5–6.0) and 5.7m (95% CI 4.1–6.6) respectively (HR = 0.80, 95%CI 0.55–1.18). 55% of pts in both arms experienced Grade 3/4 adverse events (AEs) with no significant differences in frequency or severity between the arms. Most common Grade 3/4 AEs were thrombocytopenia, seizures, hyperglycaemia and diarrhoea. CONCLUSION: VERTU demonstrated that a novel treatment strategy for patients with de novo uMGMT GBM was feasible and tolerable. The observed 6mPFS and PFS were similar in both arms. Overall survival and other endpoints will be presented. Central MRI review, biomarker analyses, including DNA repair and methylation signature analyses are ongoing. (ANZCTR#ACTRN12615000407594).